Bose Bandhu aur bhartiya Swatantrata : Ek Kareebi Ka Vivran. - Bose, Madhuri (SAGE Publications, 2017)
An insider's view of the Bose Brothers (Sarat and Subhas)-a glimpse of their, trials and tribulations, and their roles as freedom fighters.